2019
DOI: 10.3390/cells9010053
|View full text |Cite
|
Sign up to set email alerts
|

On ATG4B as Drug Target for Treatment of Solid Tumours—The Knowns and the Unknowns

Abstract: Autophagy is an evolutionary conserved stress survival pathway that has been shown to play an important role in the initiation, progression, and metastasis of multiple cancers; however, little progress has been made to date in translation of basic research to clinical application. This is partially due to an incomplete understanding of the role of autophagy in the different stages of cancer, and also to an incomplete assessment of potential drug targets in the autophagy pathway. While drug discovery efforts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 132 publications
2
25
0
Order By: Relevance
“…This is consistent with evidence reported previously that the LC3-II accumulation may be associated with elevated pH or impaired protease activity in the lysosome or defective degradation of LC3-PE on autophagosomal structures the suppression of ATG4B activity [ 48 ]. This result agreed with previous studies that reported the crucial role of ATG4B in autophagosome elongation and maturation steps of autophagic regulation that involved cancer cell differentiation and proliferation [ 49 , 50 ]. Therefore, ATG4B inhibition through the combination therapeutic strategy may serve as a new cancer therapeutic strategy tool to diminish autophagic flux and enhance chemotherapeutic drugs’ anti-tumor effect.…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with evidence reported previously that the LC3-II accumulation may be associated with elevated pH or impaired protease activity in the lysosome or defective degradation of LC3-PE on autophagosomal structures the suppression of ATG4B activity [ 48 ]. This result agreed with previous studies that reported the crucial role of ATG4B in autophagosome elongation and maturation steps of autophagic regulation that involved cancer cell differentiation and proliferation [ 49 , 50 ]. Therefore, ATG4B inhibition through the combination therapeutic strategy may serve as a new cancer therapeutic strategy tool to diminish autophagic flux and enhance chemotherapeutic drugs’ anti-tumor effect.…”
Section: Resultssupporting
confidence: 93%
“…108 Thus, the value of isoform-specific versus pan-ATG4 inhibition to target autophagy is still debated and will require additional research. 109 Similar to other autophagy targets, several ATG4B inhibitors have been reported over the past decade, but none is yet in clinical development. 110,111 Activating/enhancing autophagy.…”
Section: Autophagy In Pdac: Translational Findingsmentioning
confidence: 99%
“…After autophagosome expansion and maturation, ATG4B is reactivated to release LC3 from the membrane junction which leads to fusion of the engulfed contents and lysosomes. 36 However, ATG4B actually promotes tumor cell migration or proliferation among several cancer types, including breast cancer, 37 pancreatic ductal adenocarcinoma, 38 colorectal cancer, 39 and prostate cancer. 40 When blocked using an inhibitor or miRNA of ATG4B , tumor cell proliferation was controlled and susceptibility towards chemotherapy was enhanced due to the repressed autophagy, in this process, pro-LC3 cannot be cleaved, and the fusion of the autophagosomes with lysosomes would also be obstructed, which means that downregulation of ATG4B is helpful to cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%